Socio-economic burden of chronic migraine in Russia - A. A. Kolbin; M. V. Naprienko; A. R. Artemenko; I. A. Vilyum; N. V. Latysheva; M. A. Proskurin; Yu. Ye. Balykina (Izdatelstvo OKI, 2019)
Introduction. Results of both clinical and epidemiological studies demonstrate a high frequency of work incapacity associated with headache, reduced socio-economic activity, low quality of life, greater number of comorbid diseases and mental disorders in patients with chronic migraine (CM) compared to those who suﬀer from episodic primary headache.Objectives. Te objective of the study was comparative assessment of the disease cost and clinical and economic consequences of using various therapeutic approaches for preventive treatment of CM from the societal perspective in the Russian Federation.Methods. Te following types of pharmacoeconomic analyses were used: disease cost analysis, budget eﬀect analysis. Models based on literature data (Scenario No. 1) and based on expert opinion (Scenario No. 2) were constructed in parallel with subsequent interpretation and discussion of the results obtained. Direct and indirect costs were considered. Efcacy criteria were clinical outcomes of the use of therapeutic options in question - change in the frequency of use of migraine-associated aid: change in the frequency of use of emergency medical care; change in the frequency of inpatient treatment.Results. CM is a disease associated with a signifcant socio-economic burden: the cost of managing a target population of 1 470 840 patients with current distribution of therapeutic approaches can reach up to 402 569 527 778 RUB with clinical and economic modeling based on literature data, and 444 918 119 377 RUB with clinical and economic modeling based on expert opinion surveys. Indirect costs constitute a signifcant proportion of the socio-economic cost of CM, estimated at 61 995 589 503 RUB to 88 794 056 961 RUB. Te use of various therapeutic approaches for treating CM can reduce the cost of the disease for the target population. Te cost of managing one patient with Botox® per year (141 820 RUB) was up to 40 % lower than the cost of preventive treatment of a patient with CM with oral medications (202 894 RUB), up to 192 % lower than the cost of managing patients without preventive treatment (414 305 RUB). Te use of Botox is associated with signifcantly smaller indirect costs in comparison with the use of other therapeutic approaches in managing patients with CM.